MANUAL THROMBOEXTRACTION IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITH ST-SEGMENT ELEVATION - A. S. Tereschenko; E. V. Merkulov; V. M. Mironov; R. M. Shakhnovich; A. N. Samko («REMEDIUM GROUP» Ltd., 2016)
Distal coronary artery embolism (DCAE) is a serious complication  of percutancous coronary intervention (PCI).  Distal embolism causes a significant reduction or even blockage of myocardial perfusion, despite the fact that blood flow in the occluded segment of the infarct-related artery is restored. According to various sources, the incidence of distal embolization associated with PCI is about 25%. Various techniques, both invasive and non-invasive, have been developed for identifying distal embolism. DCAE during PCI is prevented with the help of different devices, among which those for thromboextraction are the most reliable. The devices can be divided into manual and rheolytic.